Controlled synthesis and luminescence properties of GdF3 with different crystalline phases and morphologies. Issue 11 (28th February 2017) - Li, Yi; Wang, Yuexin; Song, Yanhua; Zhou, Xiuqing; Zheng, Keyan; Sheng, Ye; Zou, Haifeng
Abstract : GdF3 with raisin-like particles, plates with dots in their centers, peanut-like particles and spherulite-like particles have been synthesized via a simple hydrothermal method with tartaric acid as an additive, by simply modulating the pH values and H2 O/ethanol ratio of the system. Abstract : GdF3 with raisin-like particles, plates with dots in their centers, peanut-like particles and spherulite-like particles have been synthesized via a simple hydrothermal method with tartaric acid as an additive, by simply modulating the pH values and H2 O/ethanol ratio of the system. The possible formation mechanisms of the particles obtained in mixed solvents and pure water are proposed based on a series of time-dependent experiments. Both hexagonal and orthorhombic phases were obtained and the factors influencing the phase transitions are discussed in detail. The luminescence properties prove that the GdF3 particles are excellent host lattices. Under ultraviolet excitation, GdF3 :Eu 3+ particles exhibit strong red emission corresponding to the 5 D0 → 7 F1 transition of the Eu 3+ ions. Furthermore, the dependence of GdF3 :Eu 3+ luminescence performances on different morphologies and phases are discussed in the present work.